Predictive modeling of g-induced loss of consciousness for entertainment theme parks - Hariharan Anushya. (2013)
Gravity-induced loss of consciousness (G-LOC) is a phenomenon that has always been a great threat to the safety of the pilots, astronauts and theme park riders. This occurs as a result of prolonged exposure to the increasing G levels leading to unconsciousness and even death in some cases. Hence a model for the G-LOC prediction would be a useful indicator for the pilots and theme park riders before they reach the G-LOC state. During high G levels there is pooling of blood in the lower extremities, draining blood away from the brain. This in turn causes low oxygen consumption by the brain finally resulting in brain ischemia. Hence the cerebral blood flow is an important parameter in the prediction of G-LOC.